2014
DOI: 10.1371/journal.pone.0114415
|View full text |Cite
|
Sign up to set email alerts
|

Edge Effects Are Important in Supporting Beetle Biodiversity in a Gravel-Bed River Floodplain

Abstract: Understanding complex, dynamic, and diverse ecosystems is essential for developing sound management and conservation strategies. Gravel-bed river floodplains are composed of an interlinked mosaic of aquatic and terrestrial habitats hosting a diverse, specialized, and endangered fauna. Therefore, they serve as excellent models to investigate the biodiversity of multiple ecotones and related edge effects. In this study, we investigated the abundance, composition, richness, and conservation status of beetle assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
1
16
0
1
Order By: Relevance
“…However, while there has historically been interest in studying community patterns at terrestrial-aquatic interfaces (e.g. Reich, 1991;O'Callaghan et al, 2013;Langhans & Tockner, 2014), characterisation of community dynamics involving complete terrestrial-aquatic shifts, as seen in IRs, has received considerably less attention (but see Moon, 1956;Plum, 2005;Steward et al, 2012). Corti & Datry (2016) describe terrestrial and aquatic invertebrate communities from the active channel and the riparian zone of intermittent and perennial reaches along a French river.…”
Section: Ecology Journalsmentioning
confidence: 99%
“…However, while there has historically been interest in studying community patterns at terrestrial-aquatic interfaces (e.g. Reich, 1991;O'Callaghan et al, 2013;Langhans & Tockner, 2014), characterisation of community dynamics involving complete terrestrial-aquatic shifts, as seen in IRs, has received considerably less attention (but see Moon, 1956;Plum, 2005;Steward et al, 2012). Corti & Datry (2016) describe terrestrial and aquatic invertebrate communities from the active channel and the riparian zone of intermittent and perennial reaches along a French river.…”
Section: Ecology Journalsmentioning
confidence: 99%
“…A transitional state, however, is but one of several theoretically possible outcomes within boundary ecotones (Turner, 2005;Matias et al, 2013;Langhans and Tockner, 2014) and, as indeed indicated by Alfaro (2006), further comparative studies are necessary in other areas dominated by Avicennia before its status can be assured, not least because her study area being temperate may differ in important respects from equivalent habitats in lower latitudes (Alfaro, 2006;Morrisey et al, 2010). It was therefore the purpose of the present work to investigate the biodiversity, abundance and nature of faunal assemblages and their metrics across seaward pneumatophore-fringe interfaces with replacing lower-shore habitats in another (and non-temperate) geographical area.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Encouraged by the EU Flood Directive, numerous well‐accepted models recommend widening the water surface via restoration of floodplains as retention areas, a measure which can be expected to reduce the risk of inundation downstream (Merz et al ; Schober et al ). Nature conservation advocates demand the restoration of ancient floodplains since these measures create and maintain ecologically valuable habitats sheltering not only a great species diversity, but rare and threatened species, too (Grevilliot & Muller ; De Nooij et al ; Eckstein et al ; Schlaghamersky et al ; Langhans & Tockner ; Nowicki et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Nature conservation advocates demand the restoration of ancient floodplains since these measures create and maintain ecologically valuable habitats sheltering not only a great species diversity, but rare and threatened species, too (Grevilliot & Muller 2002;De Nooij et al 2006;Eckstein et al 2006; Author contributions: AG conceived the research, supervised the field work and the database; MK emptied traps, designed the database, evaluated data preliminarily; AG, RS analyzed the data and wrote the paper. Schlaghamersky et al 2008;Langhans & Tockner 2014;Nowicki et al 2015).…”
Section: Introductionmentioning
confidence: 99%